Green gifts from abroad? FDI and firms' green management - Peter Kannen; Finn Ole Semrau; Frauke Steglich (Kiel Institute for the World Economy (IfW), 2021)
Improvements of firms' environmental performance crucially determine the speed of a country's green economic transformation. In this paper, we investigate whether firms with foreign ownership are more likely to adopt 'green' management practices, which determine the capability to monitor and improve a firm's impact on the environment. By using multi-country firm-level data, we show that foreign ownership increases the likelihood of implementing green management practices. Considering country heterogeneity, we reveal that only firms based in more developed economies and in countries with better environmental performance benefit from foreign direct investment, while this is not the case for firms based in less developed economies or countries with weak environmental performance. In addition, we find that the effect is more robust for manufacturing sector firms than for service sector firms. Overall, our results suggest that foreign ownership can contribute towards a country's green economic transformation.
Keywords: F21; F64; M10; Q56; 330; Foreign direct investment; Green/environmental management; Green economic transformation; Emerging markets